The Impact of Training on Earnings: Differences Between Participant Groups and Training Forms - Anja Kuckulenz; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
While there is a broad literature on the general wage effect of training, little is known about the effects of different training forms and about the effects for heterogeneous training participants. This study therefore adds two aspects to the literature on earnings effects of training. First, the earnings effect of training is calculated for different ?types? of employees, i.e. discriminating between qualification level, experience, job tenure, and other attributes. Second, we distinguish between the earnings impact of external and internal training. For our analysis, we use the ?Qualification and Career survey?, a rich German data set with information on 0.1 percent of all individuals employed in Germany in 1998/1999. We use a one-step full-information maximum likelihood and a two stage least squares estimation to regress the impact of training participation on earnings correcting for the endogeneity of training participation. By using a broad list of employee and employer characteristics, we try to avoid omitted variable bias. We find the training earnings markup to be positively correlated with qualification and experience. The analysis of internal and external training reveals that this result is driven by external training only. Internal training does not have a significant earnings effect. The correction for selection into training leads to an increase in the training coefficients and a decrease of its significance.
Keywords: J31; C31; J24; 330; continuing training; returns to training; endogeneity; employee heterogeneity; training forms; Weiterbildung; Bildungsertrag; Lohn; Qualifikation; Erwerbsverlauf; Schätzung; Deutschland